THE PATTERNS OF TOURISM MANAGEMENT IN HOT SPRING SITES IN THE WESTERN THAILAND - Chuamuangphan, Nipon (PEOPLE: International Journal of Social Sciences, 2016)
This research aimed to study the patterns of tourism management in hot spring sites in the western Thailand. The study was conducted using qualitative approach, in collaboration with participation from local communities. The fieldwork combines varied sources of data gathering techniques including in-depth interviews, focus groups, surveys, and observations. The samples were stakeholders in relation to tourism development such as governmental organizations, entrepreneurs, local shop owners, community leaders and members, and individual persons relevant to management of three hot spring destinations in western Thailand. The collected data from interviews were analyzed, interpreted and reported using content analysis and descriptive explanation methods. The results showed that: 1) There were, three sites grouped that were different from each other: 1) be managed by local community; 2) be managed by sub-district organization and 3) be managed by forestry department. 2) All of the three representative hot spring sites, in fact, were outstanding in terms of their local identities and natural resources which were suitable for developing into tourism destinations. However, they did not deeply focused to be used for health tourism at the sites. 3) In terms of tourism patterns, the three sites were considered as health tourism destination which combined health tourism activities with other tourism resources and activities both in the area and nearby the destinations in order to encourage the local to use the hot springs for tourism activities. 4) The patterns of tourism management in hot spring for health tourism development in each study sites were different depending on the organizations that managed the area. For example, some sites were took care by the national park. Some of them were controlled by the Tambon Administration Organization (TAO). And some sites were locally managed by the community members. As a result, the levels of participation in each site were different. There was only one, has been managed by local community, participation level of local residents was higher than the other authorities, for instance. Moreover, a hot spring tourism master plan should be launch as a guideline for tourism planning and management of hot spring destinations throughout Thailand. This master plan would help all destinations to be better plan and set the appropriate directions of hot spring tourism development, which would benefit to the sustainability of the resources and the conservation of local identity and uniqueness.